Crucial Factors for the Acceptance of a Computerized National Medication List - Hackl, W.O.; Hoerbst, A.; Duftschmid, G.; Gall, W.; Janzek-Hawlat, S.; Jung, M.; Woertz, K.; Dorda, W.; Ammenwerth, E. (Applied Clinical Informatics, 2014)
Objective: The objective of this paper is to present crucial factors among registered doctors and pharmacists for acceptance of the Austrian ’e-Medikation’ system which is aimed at providing, on a national level, complete and recent information on all the medication that were prescribed or dispensed to a patient.Methods: As the accompanying formative evaluation study of the pilot project showed different overall acceptance rates among participating physicians and pharmacists, a decision tree analysis of 30 standardized survey items was performed to identify crucial acceptance factors.Results: For the physicians’ group, only two items (fear of improper data use and satisfaction with software support) were crucial for overall e-Medikation acceptance. The analysis of the pharmacists’ data resulted in five crucial factors primarily focusing on functional aspects and the perceived benefits of e-Medikation.Conclusion: The results indicate that the acceptance among physicians and pharmacists depends on quite different factors. This must be taken into account during the planned rollout of e-Medikation or of comparable products.
Keywords: Evaluation studies; medical order entry systems; prescription; questionnaire